An Exceptional Etiology of a Rare Disease: Pneumatosis Intestinalis in the Intensive Care Unit due to Chronic Graft-Versus-Host Disease - Taner Çalışkan; Hüseyin Özkök; Murat Küçük; Beril Turan Erdoğan; Vedat Uygun; Yusuf Savran; Bilgin Cömert (Galenos Yayinevi, 2021)
Pneumatosis intestinalis (PI) is a rare disease, which presents a wide range of severity. Numerous etiologies, including trauma, inflammation, infections, autoimmunity, drugs, and mechanical procedures, gave rise to this complication. Abdominal computerized tomography is the preferred diagnostic tool with high sensitivity. The diagnosis depends on free air detection in the intramural portion of the gastrointestinal system and main and intrahepatic branches of the portal venous structures. However, the exact mechanism is unknown. The clinical scenario may vary from benign to life-threatening. One of the etiological factors that cause PI is the chronic graft-versus-host disease (cGVHD), which must be considered in patients with solid organ or hematological malignancies. Especially, patients who received long-term immunosuppressive therapies and were diagnosed with cGVHD are prone to developing a PI. Many patients experience unnecessary operational risks if underdiagnosed. A multidisciplinary approach by the primary physician, general surgeon, and radiology specialist is necessary for the proper treatment of these patients. This case report aimed to discuss the clinical presentation of PI in the course of cGVHD in the intensive care unit.